The Influence of Social Media on Adolescent Sexual Behavior : Retrospective Analysis - Gonçalves, Marilia Juvi (Journal of Health, Medicine and Nursing, 2024)
In this modern era, the internet has become part of a person's basic needs. The internet has many benefits in learning for everyone, because with the internet we can find out a lot of information and knowledge that we have never known before. Usually, the goal of teenagers to access the internet is to access social media. Basically, social media is a place where everyone can communicate, express themselves, disseminate information and so on, therefore teenagers and minors should be given direction or supervision when using social media, because behind the benefits, there are also many negative things that exist on social media such as internet access to pornography can be one of the sources of premarital sexual behavior occurring.  The purpose of writing the article is to find out the influence of social media on adolescent sexual behavior. This article method uses library research, which is a method of collecting data by understanding and studying theories from various literature related to research. Based on the results of the analysis that has been carried out on 7 international articles, it was found that adolescents have very high exposure to social media with adolescent sexual behavior and unhealthy use of social media such as viewing pornographic content, adolescents will imitate and do what they see. The more experiences of hearing, seeing, and experiencing sexual behavior, the stronger the stimulus that can encourage the emergence of sexual behavior. One of the negative impacts of the use of social media is free sex. One of the groups that is very affected by social media is teenagers.